Peningkatan Keterampilan Menulis Melalui Kegiatan Motorik Halus Di RA Nur Hasanah Banua Budi - Mahmudah Mahmudah; Ujang Maulana Yusup (CV. ITTC INDONESIA, 2025)
This study aims to improve early childhood writing skills through fine motor activities in Group B at RA Nur Hasanah Banua Budi. The method used is Classroom Action Research, conducted in two cycles, each consisting of the stages of planning, action, observation, and reflection. The research subjects were 16 children aged 4–6 years, consisting of 8 boys and 8 girls. Data were collected through observation sheets and analyzed using descriptive quantitative methods. The results showed an improvement in children's writing abilities in each cycle. The average score increased from 2.0 in the pre-cycle stage to 2.64 in Cycle I and reached 3.0 in Cycle II. This improvement was observed in five writing skill indicators: the ability to trace letters, follow lines, imitate writing, identify letters, and write simple words or sentences. The gradual implementation of fine motor activities proved effective in enhancing hand-eye coordination, concentration, and children's interest in writing. Therefore, fine motor activities can serve as an enjoyable and effective alternative learning strategy to enhance early childhood writing skills. Teachers are encouraged to integrate fine motor activities into daily learning to support the optimal development of early literacy.